2020
DOI: 10.1002/hed.26068
|View full text |Cite
|
Sign up to set email alerts
|

Restoring apoptosis dysregulation using survivin inhibitor in nasopharyngeal cancer

Abstract: Background: Restoring apoptosis dysregulation via survivin inhibition has been investigated in several cancers. In Epstein-Barr Virus (EBV)-driven nasopharyngeal cancer (NPC), virally induced oncogenes can upregulate survivin. Therefore, we seek to investigate the therapeutic efficacy of YM-155 (a survivin inhibitor) in NPC, both in vitro and in vivo models. Methods: Cytotoxicity, apoptosis, and active-caspase 3 expression assays were performed. Results: Both NPC tissue and cells expressed high levels of survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…BIRC5 is highly expressed in a variety of tumor tissues, while its expression level is very low or not expressed in normal tissues. Some studies have con rmed that BIRC5 is involved in the malignant transformation of tumor cells and the physiological process of anti-apoptosis, suggesting that BIRC5 gene can be used as an important target for anti-tumor therapy [21]. In this study, BIRC5 expression in LGG normal tissues and tumor tissues was compared and analyzed.…”
Section: Discussionmentioning
confidence: 97%
“…BIRC5 is highly expressed in a variety of tumor tissues, while its expression level is very low or not expressed in normal tissues. Some studies have con rmed that BIRC5 is involved in the malignant transformation of tumor cells and the physiological process of anti-apoptosis, suggesting that BIRC5 gene can be used as an important target for anti-tumor therapy [21]. In this study, BIRC5 expression in LGG normal tissues and tumor tissues was compared and analyzed.…”
Section: Discussionmentioning
confidence: 97%
“…The NDC80 complex, including the main elements of NDC80, SPC24, and SPC25, is highly expressed in various tumors and cooperatively promotes the invasion and metastasis of tumor cells (Alushin et al, 2012;Umbreit et al, 2012). BIRC5 is a negative regulatory protein that inhibits tumor cell apoptosis and promotes cell proliferation (Cho et al, 2020;Shi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that anti-survivin siRNA enhances apoptosis and overcomes chemotherapy resistance in vitro [59] and in vivo [60]. In NPC, Shi et al reported that the YM-155, which is a survivin inhibitor, induces apoptosis of NPC cells and inhibits tumor growth in the mouse model [61]. Apart from the inhibition of apoptosis, cell proliferation is also related to survivin.…”
Section: Discussionmentioning
confidence: 99%